Testing the effectiveness of disinfectant protocols for soiled footwear - Young, S.D.; McNeill, M.R.; Saville, D.J. (New Zealand Plant Protection, 2008)
Footwear carried by international air travellers arriving in New Zealand is subject to inspection and if necessary cleaning and disinfecting by MAFBNZ quarantine inspectors A study to evaluate the effectiveness of disinfectant treatment was carried out on three different types of footwear (running shoes gumboots and tramping boots) cleaned following observed MAFBNZ procedure (dip) and following a 10 minute soak Two disinfectant treatments (VirkonTM and TriGene AdvanceTM) were compared with a surfactant (polysorbate 80) and water only Soles were swabbed for microbes before and after washing and culturable bacteria and fungi per cm2 were enumerated Disinfectant treatments reduced bacteria numbers by 99 compared with 98 for both water and surfactant treatments VirkonTM was the best treatment for bacteria both with the standard dip and the 10 minute soak but it was not significantly better than the other treatments Soaking also reduced bacterial numbers compared to the dip treatment but not significantly For fungi the two disinfectants surfactant and water yielded similar reductions (97) Soaking reduced fungal numbers compared to the dip treatment but this was not quite significant (P0051)